Cultural and political imaginaries in Putin's Russia - Bernsand, Niklas, 1973-; Törnquist Plewa, Barbara (Eurasian studies library, 2019)
"In Cultural and Political Imaginaries in Putin's Russia scholars scrutinise developments in official symbolical, cultural and social policies as well as the contradictory trajectories of important cultural, social and intellectual trends in Russian society after the year 2000. Engaging experts on Russia from several academic fields, the book offers case studies on the vicissitudes of cultural policies, political ideologies and imperial visions, on memory politics on the grassroot as well as official levels, and on the links between political and national imaginaries and popular culture in fields as diverse as fashion design and pro-natalist advertising. Contributors are Niklas Bernsand, Lena Jonson, Ekaterina Kalinina, Natalija Majsova, Olga Malinova, Alena Minchenia, Elena Morenkova-Perrier, Elena Rakhimova-Sommers, Andrei Rogatchevski, Tomas Sniegon, Igor Torbakov, Barbara Törnquist-Plewa, and Yuliya Yurchuk"--